Implementation Of Integration Of Science With Islamic Religious Education In The Integrated Islamic Primary School Al-Fityah Pekanbaru - Irawati, Irawati; Setyaningsih, Rini (EL-EMIR Institute, 2024)
The aim of this research is to determine the model of integration of science and Islamic religious education at Al-Fityah Integrated Islamic Elementary School Pekanbaru and to determine the implementation of the integration of science and Islamic religious education at Al-Fityah Integrated Islamic Elementary School Pekanbaru. Research Method This research uses a non-probability sampling technique. Data analysis techniques with steps in qualitative data analysis are data reduction, data display or data presentation, and drawing conclusions. First research results, Curriculum Model, there are three types of curriculum models at SDIT Al-Fityah Pekanbaru, namely: Ministry of National Education curriculum, material curriculum, and SDIT specialty curriculum, each of which complements one another. Second, Implementation of the Integration of Science and Islamic Religious Education, Implementation of Science with Islamic religious education at SDIT Al-Fityah Pekanbaru through three stages, namely: The first stage is planning by preparing the syllabus, RKPS and student books, the second stage is implementation by dividing it into three phase, initial phase or introduction, middle phase or emphasis on material, and final phase provides conclusions, and the third phase is the evaluation phase by assessing the process and assessing learning outcomes, the assessment technique is test or non-test.